2011
DOI: 10.1016/j.jmii.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic characterization of atypical enteropathogenic Escherichia coli serotypes isolated from children with and without diarrhea

Abstract: The characteristics of the atypical EPEC serotypes from children with diarrhea were significantly different from those without diarrhea. The compilation of data on atypical EPEC strains presented here indicates the importance of a combined approach of conventional and molecular tests to study the virulence and epidemiology of EPEC serotypes in human subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
3
6
1
Order By: Relevance
“…Animals can be reservoirs of atypical EPEC, in contrast to typical EPEC, in which humans are the sole reservoir [61], indicating that food chain and animal contact could be other factors for the dissemination of resistant DEC among pediatrics in Qatar. In contrast with our findings, studies from Iraq and India documented atypical EPEC harboring bfpA without eaeA gene [34,56]. Early studies conducted in England and Peru have shown that atypical EPEC is often found in children with and without diarrhea, and the pathogenic potential of atypical EPEC strains has been speculative in the past [62,63].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Animals can be reservoirs of atypical EPEC, in contrast to typical EPEC, in which humans are the sole reservoir [61], indicating that food chain and animal contact could be other factors for the dissemination of resistant DEC among pediatrics in Qatar. In contrast with our findings, studies from Iraq and India documented atypical EPEC harboring bfpA without eaeA gene [34,56]. Early studies conducted in England and Peru have shown that atypical EPEC is often found in children with and without diarrhea, and the pathogenic potential of atypical EPEC strains has been speculative in the past [62,63].…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to our findings, in the MENA region, atypical EPEC strains have been the most manifested in Iran (100%), Iraq (66.7%) and Kuwait (95.6%) [34,55,56]. They have been also reported in other countries worldwide, such as Brazil, North-West Italy, Melbourne, India [56][57][58][59][60]. In agreement with our findings, the atypical EPEC organisms that possess eae alone have been reported to be more prevalent in both developing and developed countries.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study from Iraq documented only atypical EPEC harboring bfpA without eaeA gene [ 22 ]. In a study conducted in Iran for both types of atypical EPEC, those harboring only eaeA and those harboring only bfpA were detected [ 23 ]. Another study from India documented the isolation of atypical EPEC (harboring only eaeA gene) from children with diarrhea and atypical EPEC (harboring only bfpA gene) from children without diarrhea in control group [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…EHEC was the most detected pathotype found in both human and water samples followed by EPEC/EHEC. These pathotypes were the most detected pathotypes in children with diarrhoea in two studies performed in Iran 7,59 and Spain 16 . EHEC is the primary cause of severe gastroenteritis and HUS outbreak in Germany 60 .…”
Section: Discussion Identification and Distribution Of Dec Pathotypesmentioning
confidence: 83%